Use of the water hyacinth (Eichhornia crassipes) in the ecological regeneration process of lentic water systems - Cathryn Sabido, Carissa (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2025)
Tesis (Sc.Mag.) –CATIE, Turrialba (Costa Rica), 2024